Al-Shabakah al-Tijārīyah li al-Sulṭanah al-Indūnīsīyah fī Qarn 15-17 M - Tjandrasasmita, Uka (Studia Islamika, 2003)
This article concerns the trade networks of the lndonesian Sultanates in the 15-78 centuries A.D. The growth and development of the trade networks was closely connected to the process of navigation and the development of sen-routes. Due to the geographical nature of the Indonesian Archipelago, trade networks were developed by people living in the area. Important research into lndonesian history from a socio-economic approach, particularly in relation to trade, has been carried out by J.C. van Leur, O.W. Wolters, Meilink Roelofsz, Rita Rose Di Meglio, amongst others. Their opinions on particular issues have been used to support the historical facts related to the topic of this article.DOI: 10.15408/sdi.v10i3.625